1998
DOI: 10.1016/s0022-3093(98)00540-7
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic properties of trivalent lanthanide ions in fluorophosphate glasses

Abstract: We describe the spectroscopic properties of the trivalent lanthanide ions Ce 3 , Pr 3 , Nd 3 , Sm 3 , Eu 3 , Gd 3 , Tb 3 , Dy 3 , Ho 3 , Er 3 , Tm 3 and Yb 3 in the¯uorophosphate glasses 75NaPO 3 ±24CaF 2 ±1LnF 3 and 75NaPO 3 ±20CaF 2 ± 5LnF 3 (where Ln lanthanide ion). Absorption and luminescence spectra are discussed. The dipole strengths of the transitions in the absorption spectrum are parametrized in terms of three X k (k 2, 4 and 6) Judd±Ofelt intensity parameters. These phenomenological parameters are u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
53
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(66 citation statements)
references
References 33 publications
(33 reference statements)
10
53
0
3
Order By: Relevance
“…Analogous observations were reported for Tm 3ϩ -doped fluorophosphate glasses. 22 In another experiment, the samples were excited using a pulsed dye laser operating at Ϸ655 nm ͑in resonance with transition 3 H 6 → 3 F 2 ) and two fluorescence bands were observed as presented in Figs. 4͑a͒ and 4͑b͒.…”
Section: ͑3͒mentioning
confidence: 99%
“…Analogous observations were reported for Tm 3ϩ -doped fluorophosphate glasses. 22 In another experiment, the samples were excited using a pulsed dye laser operating at Ϸ655 nm ͑in resonance with transition 3 H 6 → 3 F 2 ) and two fluorescence bands were observed as presented in Figs. 4͑a͒ and 4͑b͒.…”
Section: ͑3͒mentioning
confidence: 99%
“…Upconversion laser emission and amplified spontaneous emission studies have been reported for Tm 3ϩ doped optical fibers and channel waveguides. 1,2,12,13 Recently a number of reports became available where detailed spectroscopic properties of Tm 3ϩ were analyzed in glasses such as fluorozirconate, 14,15 fluoroindate, 16 -18 fluorophosphate, 19,20 fluoroindogallate, 21 and silicate. 22 Each glass host presents certain characteristics that favor specific applications.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, fluorophosphate glasses have been recently investigated because of their potential as a laser host material and optical amplifier. 19,[23][24][25] In this work, tungstate fluorophosphate glasses have been chosen as host matrices to study the spectroscopic properties of Tm 3ϩ . Two previous articles report some of the physical properties of these glasses.…”
Section: Introductionmentioning
confidence: 99%
“…For example, fluorophosphate glasses have been investigated because of their potential as laser materials and optical amplifier media. 9,14,15 Here we present results for tungstate fluorophosphate ͑TFP͒ glass that is a new emerging photonic material. Recently, TFP glasses have been considered as host materials for fluorescence studies of RE ions and for nonlinear optics.…”
Section: Introductionmentioning
confidence: 95%
“…In particular, thulium ͑Tm 3+ ͒ and neodymium ͑Nd 3+ ͒ ions are recognized as efficient RE ions for obtaining laser emission and frequency up-conversion ͑UC͒. 1,2 A large number of reports are available where detailed spectroscopic properties of Tm 3+ and Nd 3+ were analyzed in glasses such as fluorozirconate, 1-4 fluoroindate, [5][6][7][8] fluorophosphate, 9,10 and silicate. 1,2,11 The investigation of ET processes between Tm 3+ and Nd 3+ was reported for different host materials.…”
Section: Introductionmentioning
confidence: 99%